Estrategias discursivas de los nuevos grupos conservadores mexicanos contra la “ideología de género” - Bernal Lugo, Ricardo (2024)
In Mexico, over the past two decades, a multitude of (neo)conservative groups staunchly opposed to sexual and reproductive rights, same-sex marriage, adoption by same-sex couples and sex education have developed new forms of organization and political advocacy and discourse that challenge a sector of society. This paper aims to analyze three groups (Frente Nacional por la Familia, Partido Encuentro Solidario and Nueva Derecha), which come from different political traditions and religious convictions. These have influenced the growth of the right-wing, accompanied by discursive strategies, which take up symbolic elements of the past adapted to new characteristics and concerns. To understand this social phenomenon, we turn to the history of conservatism in Mexico and also analyze some current conservative discourses as strategies to spread out, based on some tools of Critical Discourse Analysis and directed to a concept that allegedly "threatens" the values that preserve the social order: gender ideology. As a result, we expose how these groups have constructed a set of narratives shared by an essential sector of the Mexican population, allowing them to influence public decisions at national and local levels in different ways.